Detailed structural and morphological characterization of ingan thin films grown by rf magnetron sputtering with various substrate temperature - Mantarcı, Asim (My University, 2019)
Indium Gallium Nitride (InGaN) thin film was grown on the GaN/p ? Si substrate using an RF magnetron sputter under condition of different substrate temperatures. Various experimental measurements were taken to comprehend effects of substrate temperature on the structure of thin film and results were analyzed. Grazing mode of XRD results confirmed that InGaN thin film has a hexagonal structure with (002) plane for 500°C and 600 °C substrate temperature. It was seen that structural parameters of thin film show a change with substrate temperature change. Reasons were discussed. Strain and stress values in InGaN thin film were calculated from experimental results and it was found that all thin film has compressive stress. Morphological parameters of thin film were measured by AFM and it was understood that these properties are varied by changing substrate temperature. Also, growth mode of some thin film was obtained to be layer-plus-island mode (Stranski-Krastanov growth mode), others was obtained to be layer by layer growth mode (Frank van der Merwe mode). SEM evaluation gives that increasing substrate temperature worsened the surface structure of InGaN thin film; it is compatible with and supports XRD results. Compositional values in InGaN thin film were found from XPS analysis. In addition to our material, carbon and oxygen have also been obtained from XPS results, as expected. Detailed morphological and structural properties of InGaN thin films have been seen to change with changing substrate temperature and we believe this plays an important role in production of InGaN based optoelectronic devices.
Keywords: thin film technology; RF magnetron sputtering; substrate temperature; Fizik, Nükleer; Mühendislik, Petrol